Titanite as an indicator of granite fertility and gold mineralization in the Xiaoqinling gold province, North China Craton - Wei, Quan; Li, Lin; Li, Sheng-Rong; Santosh, M.; Alam, Masroor; Chen, Zhen-Yu; Li, Min-Gang; Chen, Xiao-Dan; Wen, Zi-Hao; Liu, Jia-Wei (Frontiers in Earth Science, 2024)
The Xiaoqinling gold province, located in the southern margin of the North China Craton (NCC), is the second largest gold-enriched region in China. In this region, the Mesozoic Huashan (HS) and Wenyu (WY) plutons are the major magmatic intrusions coeval with gold mineralization, although they show contrasting characteristics in the distribution of gold. In this study, we use geochemical features of titanite determined by LA-ICP-MS and EPMA analyses and elemental mapping to decipher the mechanisms that led to the difference in gold enrichment related to the two plutons. Titanite from the Wenyu granitic pluton exhibits significantly higher (La/Sm)N, (La/Yb)N, ΣLREE/ΣHREE ratios, and ΣREE concentration and slightly higher (Gd/Yb)N values than those of the Huashan Pluton, suggesting that the Wenyu pluton might have experienced more complex magmatic evolution, widespread hydrothermal alteration, and higher silica activity in the melt than the Huashan pluton. The titanite grains from the Huashan pluton show higher (Nb/Ta)N and (Lu/Hf)N values and significantly lower Zr concentration than those of the Wenyu pluton. The titanite grains from the Wenyu pluton show higher vanadium and gallium concentrations and Fe/Al ratio than those of the Huashan pluton, indicating comparatively higher fo2. Furthermore, the titanite grains from Wenyu pluton indicate higher water content in the magma. In addition, magma mingling and magmatic hydrothermal fluids derived from the crust/mantle are critical sources for ore-forming materials. These results suggest that the Wenyu pluton is more conducive to gold migration and enrichment than the Huashan pluton.